answersLogoWhite

0

The basic principle is that (with some caveats for certain operations) you can apply the SAME operation to both sides of an equation. For instance, you can add the same number to both sides, divide both sides by the same number (watching out that you don't accidentally divide by zero), take the square root on both sides, etc.

User Avatar

Wiki User

7y ago

Still curious? Ask our experts.

Chat with our AI personalities

ProfessorProfessor
I will give you the most educated answer.
Chat with Professor
TaigaTaiga
Every great hero faces trials, and you—yes, YOU—are no exception!
Chat with Taiga
BlakeBlake
As your older brother, I've been where you are—maybe not exactly, but close enough.
Chat with Blake

Add your answer:

Earn +20 pts
Q: Who do you Rearrange equations?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Math & Arithmetic

How do you rearrange algerberic equations?

Here is a two-step process that works every time: 1). From a book, a teacher, or a knowledgeable acquaintance, learn the permissible operations. 2). Apply the operations according to the rules you have learned.


How are Laplace transforms useful?

Some differential equations can become a simple algebra problem. Take the Laplace transforms, then just rearrange to isolate the transformed function, then look up the reverse transform to find the solution.


How do you do Linear and Exponential Equations?

That completely depends on exactly what operation you have in mind. You can "do" several different types of operations to an equation, such as solve it, differentiate it, rearrange it, factor it, or apply the same arithmetic procedure to both sides of it. But you can't "do" the equation.


What is the process of solving systems of equations when you add the two equations together in hopes of eliminating a variable?

You need to make the terms on each side as much alike as possible in the two equations for easy thought process. For example, Let us look at the following two equations. a * b = c * d --- (1) x * d = k * a --- (2) Rearrange (2) so that 'd' is on the right side of the equation and 'a' on the left. a * k = x * d --- (3) Divide (1) by (3): b / k = c / x --- (4) I have eliminated two variables from (1) and (2) to form equation (4). ===========================


How would i Solve the system x plus y equals 9comma -3 equals 2x - y?

Rearrange the second equation to read 2x - y = -3Add the two equations: 3x = 6:Divide by 3: x = 2 so y = 7